Development of Brand Personality Measure: An Application for Vietnamese Context - Hang, Le Thi Minh; Truong-Dinh, Bao Quoc (Asian Journal of Empirical Research, 2018)
Although a considerable amount of research has been conducted to conceptualize brand personality, no study yet developed a brand personality measure in Vietnam. This study responds to criticism of Aaker (1997)’s brand personality measure that embraces other aspects besides personality, we applied the pure definition of personality and developed a brand personality scale in Vietnamese context that consists only personality items. Vietnamese (n=2465) participated in a study with sixteen brands in three different consumption situations. The results show the Vietnamese brand personality scale have the affinity with the Big-Five human personality dimensions (Extraversion, Agreeableness, Conscientiousness, Neuroticism, and Openness). The findings suggest that the scale can be applied in Vietnam in future research and managerial implications regarding the use of brands are discussed.